The Implementation of MOORA Methods to Support the Refinement of Decision Priority System in Information Technology - Fanni Rahmah Tsani; Umi Chotijah (Jurnal Riset Informatika, 2022)
Maintenance of information and communications technology scoped on the Lamongan Regency Government is the responsibility of the Lamongan Regency Communications and Information Department. The application of information technology is closely related to the problems that appear, such as Communication Network Interruption/Damage. In this case, the report is provided by the user via WhatsApp message, and no single point of contact is used for delivery, retard the refinement process and making it difficult for technicians to prioritize refinement. In this study, the authors built a decision-supporting to assist technicians in prioritizing refinement. The Multi-Objective Optimization Based Ratio Analysis (MOORA) method is appropriate for this study as it allows us to perform the ranking process based on different weighting attributes. The calculation process of the MOORA method is based on specified criteria and weightings. Criteria are the type of damage, risk of a complaint, duration of the claim, and type of service. In one day, the three regional apparatuses with the highest scores are selected, and recommendations for prioritized refinement are provided. In this study, we found that samples with high criterion weights and scores tended to be prioritized over other samples. The results MOORA calculated show the library service as the best alternative with a value of 0.396 on ten regional apparatus tested.